Salt-Mediated Stiffening, Destruction, and Resculpting of Actomyosin Network - Gurmessa, Bekele J.; Rust, Michael J.; Das, Moumita; Ross, Jennifer L.; Robertson-Anderson, Rae M. (Frontiers in Physics, 2021)
Cells dynamically change their viscoelastic properties by restructuring networks of actin filaments in the cytoskeleton, enabling diverse mechanical processes such as mobility and apoptosis. This restructuring is modulated, in part, by actin-binding proteins, such as myosin II, as well as counterions such as Mg^2+ and K^+. While high concentrations of Mg^2+ can induce bundling and crosslinking of actin filaments, high concentrations of K^+ destabilize myosin II minifilaments necessary to crosslink actin filaments. Here, we elucidate how the mechanics and structure of actomyosin networks evolve under competing effects of varying Mg^2+ and K^+ concentrations. Specifically, we couple microfluidics with optical tweezers microrheology to measure the time-varying linear viscoelastic moduli of actin networks crosslinked via myosin II as we cycle between low and high Mg^2+ and K^+ concentrations. Our complementary confocal imaging experiments correlate the time-varying viscoelastic properties with salt-mediated structural evolution. We find that the elastic modulus displays an intriguing non-monotonic time dependence in high-salt conditions, that correlates with structural changes, and that this process is irreversible, with the network evolving to a new steady-state as Mg^2+ and K^+ decrease back to their initial concentrations.